Analisis Pengaruh Pengeluaran Pemerintah, Investasi, Angkatan Kerja dan Human Capital Investment di Provinsi Jawa Tengah Tahun 2019-2020 - Alfalerina Puspa Millenia; Maulidyah Indira Hasmarini (Universitas Batanghari Jambi, 2023)
Government spending, investment, labor force and human capital investment are important components in building economic growth. This study aims to analyze the effect of government spending on economic growth, investment on economic growth, the workforce on economic growth and human capital investment on economic growth in Central Java Province in 2019-2020. Data on government spending, investment, workforce, human capital and economic growth are obtained from an online database published by the Central Bureau of Statistics (BPS). The method used in this study is multiple linear regression analysis. The research shows that panel data regression estimation with the selected model is the Fixed Effect Model (FEM) which shows that the results of Government Expenditure and Human Capital Investment have a significant effect on economic growth. Meanwhile, Investment and Labor Force have no effect on economic growth in Central Java.